2015
DOI: 10.1097/mnh.0000000000000117
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk in glomerular injury and repair

Abstract: Purpose of review The glomerulus is a unique structure required for filtration of blood, while retaining plasma proteins based on size and charge selectivity. Distinct cell types form the structural unit that creates the filtration barrier. Structurally, fenestrated endothelial cells line the capillary loops and lie in close contact with mesangial cells. Podocytes are connected by specialized intercellular junctions known as slit diaphragms and are separated from the endothelial compartment by the glomerular b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 40 publications
3
62
0
Order By: Relevance
“…Cellular cross-talk is vital for maintenance of the integrity and permselectivity of the glomerular barrier and is generally very challenging to mimic in vitro. 10,11 This organoid model is useful as an advanced 3D screening in vitro model where various stressors, stimuli, and toxins can be used to affect relevant cells types, their cross-talk, and their properties, and where compounds could be identified to reverse the injured phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cellular cross-talk is vital for maintenance of the integrity and permselectivity of the glomerular barrier and is generally very challenging to mimic in vitro. 10,11 This organoid model is useful as an advanced 3D screening in vitro model where various stressors, stimuli, and toxins can be used to affect relevant cells types, their cross-talk, and their properties, and where compounds could be identified to reverse the injured phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…9 Notably, there are still no adequate in vitro cellular models to mimic glomerular function that faithfully recapitulates the inherent in vivo properties of podocytes and the cellular cross-talk taking place in the glomerulus. 10,11 Isolation and culture of glomeruli result in outgrowth of a fraction of podocytes that have re-entered the cell cycle. These cells regain a limited proliferation potential and can be transiently maintained in culture; this subculture does, however, induce dedifferentiation as reflected by loss of foot processes and differentiation-specific markers such as nephrin (NPHS1) and synaptopodin (SYNPO).…”
mentioning
confidence: 99%
“…These data emphasize the importance of a functional microvasculature and accompanied hemodynamics to boost glomerular filtration barrier formation and kidney organoid maturation. The crosstalk between the glomerular endothelium and podocytes via the GBM is a known hallmark for developing and maintaining a filtration barrier function [65]. All taken together, 3D differentiation protocols resulting in self-organizing nephrons that contain subsets of renal epithelial and endothelial cells will more closely resemble the glomerular filtration barrier.…”
Section: Modeling Ns Using Stem Cellsmentioning
confidence: 99%
“…Researchers have found ETBR was mainly distributed in vascular and glomerular endothelial cells, whereas ETAR was mainly distributed in smooth muscle cells and MCs [10]. Reports have shown that MCs and endothelial cells interacted in the kidney [11,12], however, studies mainly focused on the ability of MCs to regulate the synthesis of ET-1 by endothelial cells, the effect of endothelial cells on MCs is rarely discussed. Based on ET-1 mainly expressed by endothelial cells and the crosstalk between endothelial cells and MC, we speculated that ETBR knockout in endothelial cells might have vital function in MC proliferation and ECM accumulation.…”
Section: Introductionmentioning
confidence: 99%